Ghana: health system review 2021. (20th October 2021) - Opoku, D; Edusei, AK; Agyei-Baffour, P; Teddy, G; Polin, K; Quentin, W
Abstract:  : A health system review provides a detailed description of a health care system and of reform and policy initiatives in progress or under development. The health system review of Ghana serves as an effort to also assess the system's performance towards the attainment of universal health coverage (UHC). A workshop was organized in 2018 to develop a template for writing the health system review of Ghana. This serves as a pilot study to test the feasibility of using a template somewhat like that of the WHO European Observatory on Health Systems and Policies for writing health system reviews of African countries. The health system review of Ghana is the first to be written for an African country modelled after the HiT reviews by the European Observatory. One key characteristics of the health system of Ghana is the introduction and reform of the national health insurance scheme (NHIS) in 2003 and 2012 respectively. About 40% of the population are enrolled and 60% enrolled are exempted from premium payments. Ghana has since 2010 scaled-up a national telemedicine programme, becoming one of the first adopters and innovators in Africa to integrate digital health technologies into mainstream health care system. Since 2018, Ghana has implemented the NHIS mobile renewal service, which allows payment of health insurance coverage using mobile money technologies. Ghana is one of the first countries to introduce a nationwide health insurance in Africa. The NHIS is one significant effort towards health systems strengthening and achieving UHC. Enrolment in in the NHIS contributes to better access to health care and improved financial protection. However, not only is population coverage low, but there is a serious concern about the system's financial sustainability. A promising approach is to improve the mobile-money based intervention through the high mobile-phone penetration rates in Ghana to enable more effective household saving arrangements towards UHC. Key messages: Ghana presents important lessons, including the introduction of a national health insurance. This contributes to better access to health care and improved financial protection. Ghana is exploiting the use of mobile phone technologies and has become one of the first adopters and innovators in Africa to integrate digital health technologies into mainstream health care system.